The Representation of Social Issue in Song â€œWe Prayâ€ by Coldplay: A sociology of literature Analysis - Alba Humam Faisal; Paulus Krisna Ferdian Pakpahan; Mira Marissa Putri Nainggolan; Sondifa Fajar Abadi Simbolon; T. Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This research discusses the social issues found in the lyrics of the song â€œWe Prayâ€ by Coldplay. The lyrics are analyzed to show how social issues are presented in the song. Song as a literaly wors not only created as a entertain people, but as a refelction reality in social. This study aims to understand the meanings and symbols in the lyrics. The method used in this research is qualitative, by collecting and analyzing data. The results show that the meanings and symbols in the song represent spirituality, solidarity, empathy, peace, and togetherness. This song also contains represent about world social condition and public struggle. Besides that, this song shows music role as media social critic and facilites that people can use to deliver the critic. This research shows that songs can be a good way to spread social awareness, not only has estetic thing, but contain social condition that happening in current era. Writer hopes, this research can give deeper understanding about connection between music and social condition. Word keys: Sprituality, solidarity, emphaty, pray, social issue